Dry Eye Disease Among Mongolian and Han Older Adults in Grasslands of Northern China: Prevalence, Associated Factors, and Vision-Related Quality of Life - Wu, Jianhua; Wu, Xiaomei; Zhang, Han; Zhang, Xiaoguang; Zhang, Jie; Liu, Yanqiu; Liu, Jun; Lu, Lu; Zhang, Song; Zhang, Guisen; Liu, Lei (Frontiers in Medicine, 2021)
Purpose: Dry eye disease (DED) is projected to have increasing public health burden in China with the ageing population. No published studies on the epidemiology of DED have been found in grasslands. We estimated DED prevalence among older adults living in grasslands of northern China and investigate its associated factors and impact on vision-related quality of life (VR-QoL). Methods: A multi-stage cluster random sampling technique was used to select Mongolian and Han participants aged over 40 from November 2020 to May 2021 in this area. An assessment of DED was done with Ocular Surface Disease Index (OSDI) questionnaire, Schirmer’s I test (ST), and Tear film break up time (TBUT). All participants completed National Eye Institute Visual Function Questionnaire (NEI-VFQ-25) assessing VR-QoL. Results: The overall age and gender standardised prevalence of DED was 34.5%, 32.6% of Monglian and 35.4% of Han. In a multivariate model, statistically significant associations were found with advancing age, female gender, smoke, anti-fatigue eye-drop use, milk products intake, number of household members, Schirmer's I test, TBUT and OSDI scores (all P < 0.05). DED was associated with lower scores on the VR-QoL (β = -0.14, P < 0.01). Similar results were observed when analyses were stratified by ethnicity. Discussion: The prevalence of DED was higher than those reported by previous studies. The novelty associated factors for DED in the grasslands area were anti-fatigue eye-drop use, milk products intake, and number of household members. DED and its components were associated with VR-QoL. Further prospective studies are needed to confirm these findings.